THE EFFECT OF ADDED LEG MASS ON ENERGY COST AND GAIT EFFICIENCY IN NON-PATHOLOGIC GAIT - Lin, S-J; Nielsen, DH; Dickman, SE; Kjellberg, BC; Mattiace, CM; Reents, TL; Shurr, DG (Physical therapy, 2000)
PURPOSE: Increased energy demand with ambulation is a concern for people with lower extremity amputation. Recently, light-weight but expensive prostheses have been used for replacement of the heavy but less costly stainless steel prostheses with the aim of reducing the energy demand. Studies on normal subjects with symmetrically added ankle weights or military boots have shown increased energy cost with walking and running. Research on asymmetrical added mass which would simulate amputee walking is limited. Whether there is a critical level of asymmetrical added leg mass which would increase the energy cost of walking has not yet been determined. Whether speed would amplify the effect remains unanswered. As preliminary research to future clinical studies, the purpose of this study was to determine the effects of asymmetrical added leg mass on the physiological responses of normal multiple speed treadmill walking. SUBJECTS: Twelve healthy male subjects from the university community were recruited (age 26 [+ or -] 5, height 1.81 [+ or -] 0.08m and weight 84.8 [+ or -] 16 kg). METHODS: A soccer style shin guard was used to apply the added mass (0, 0.45, 1.36 and 2.27 kg) to the center of mass of one lower leg. Four test sessions were randomized on separate days according to added leg mass. The test protocol consisted of successive four minute walking exercise stages at five progressive treadmill speeds (53.64, 67.05, 80.46, 93.87 and 107.3 m/min). During treadmill walking, oxygen consumption was determined with a metabolic cart and heart rate by ECG radiotelemetry. Gait efficiency was defined as energy cost per meter traveled. ANALYSIS AND RESULTS: A two-way (mass, speed) repeated measures analysis of variance with follow up 0 kg versus added mass comparisons was used. The analysis showed a significant interaction effect for energy cost. Simple effect analysis indicated nonsignificant between mass comparison at the three lower speeds but significant energy cost differences for 0 versus 2.27kg at the two higher speeds. For gait efficiency, there was no interaction effect. Follow-up main effect analysis for the 0 kg versus 2.27kg comparison showed a significant difference. CONCLUSIONS: The observed increased energy cost and decreased gait efficiency indicated a critical level of added leg mass exists for normal subject walking. Walking speed appeared to amplify the effect of added mass on energy cost. In order to conserve energy cost and optimize gait efficiency, the critical level of lower extremity prosthesis mass needs to be investigated for amputee walking.